2023
DOI: 10.3390/genes14020278
|View full text |Cite
|
Sign up to set email alerts
|

PyuARF16/33 Are Involved in the Regulation of Lignin Synthesis and Rapid Growth in Populus yunnanensis

Abstract: (1) Background: Lignin is a unique component of the secondary cell wall, which provides structural support for perennial woody plants. ARFs are the core factors of the auxin-signaling pathway, which plays an important role in promoting plant growth, but the specific relationship between auxin response factors (ARFs) and lignin has not been fully elucidated with regard to rapid plant growth in forest trees. (2) Objectives: This study aimed to investigate the relationship between ARFs and lignin with regard to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Similarly, in both Populus and Populus yunnanensis , which have 19 chromosomes, the ARF genes were distributed on 16 chromosomes, and the distribution of genes on different chromosomes was also uneven. Chromosome 1 was found to be the longest in both Populus and Populus yunnanensis , but it had fewer ARF genes [ 12 , 58 ]. The analysis indicated that ARF genes are distributed similarly on the chromosomes of woody plants, and the number of ARF genes on each chromosome is independent of chromosome length.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in both Populus and Populus yunnanensis , which have 19 chromosomes, the ARF genes were distributed on 16 chromosomes, and the distribution of genes on different chromosomes was also uneven. Chromosome 1 was found to be the longest in both Populus and Populus yunnanensis , but it had fewer ARF genes [ 12 , 58 ]. The analysis indicated that ARF genes are distributed similarly on the chromosomes of woody plants, and the number of ARF genes on each chromosome is independent of chromosome length.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin (AUX) is a core factor in the auxin signaling pathway, mainly in the form of IAA in plants (Zhao, 2010), and its signal transduction pathway is mainly regulated by ARFs and Aux/IAA (Guilfoyle & Hagen, 2007). As a vital plant hormone, IAA is involved in almost every aspect of plant growth and development (Hu et al., 2023). For example, IAA and its polar transport originate from young plant organs (Aloni et al., 2006) and regulate the root development of Arabidopsis (Teale et al., 2005); SlIAA9 is involved in leaf morphogenesis of tomato (Wang et al., 2005).…”
Section: Discussionmentioning
confidence: 99%